Discontinuous properties of current-induced magnetic domain wall depinning - Hu, X. F. (Nature Publishing Group, 2013)
The current-induced motion of magnetic domain walls (DWs) confined to nanostructures is of great interest for fundamental studies as well as for technological applications in spintronic devices. Here, we present magnetic images showing the depinning properties of pulse-current-driven domain walls in well-shaped Permalloy nanowires obtained using photoemission electron microscopy combined with x-ray magnetic circular dichroism. In the vicinity of the threshold current density (J(th) = 4.2 × 10(11) A.m(−2)) for the DW motion, discontinuous DW depinning and motion have been observed as a sequence of “Barkhausen jumps”. A one-dimensional analytical model with a piecewise parabolic pinning potential has been introduced to reproduce the DW hopping between two nearest neighbour sites, which reveals the dynamical nature of the current-driven DW motion in the depinning regime.